STRATEGI KOMUNIKASI ASOSIASI PETANI TEMBAKAU INDONESIA DALAM PEMBERDAYAAN PETANI TEMBAKAU DI KABUPATEN TEMANGGUNG - , NURYANTI; , Dr. Subejo, S.P,M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research is aimed to analyze forms and mechanism of tobacco farmerâs empowerment developed by the Indonesian Tobacco Farmers Association (APTI) Temanggung, it investigates the communication strategy offered by APTI Temanggung and analyzes tobacco farmersâ independence as the result of the empowerment program. The research was conducted in Temanggung Regency. Method of research used was mixed methods by giving priority to qualitative approach supported by the quantitative approach and data usage. The result shows that the forms of empowerment done by APTI were facilitating by using different empowerment mechanism for each program. APTI Temanggung has not got written communication strategy yet however their strategy has concerned and applied six elements of communication strategy namely having purpose, target audience, desired behavior, message, credible media and evaluation. Attained material independence is indicated by the ability to fulfill basic need and children school necessity